Customer Experience and Behavioral Intentions: The Mediation Role of Customer Perceived Value - Edem Amenuvor, Fortune; Owusu-Antwi, Kwasi; Basilisco, Richard; Seong-Chan, Bae (International Journal of Scientific Research and Management (IJSRM), 2019)
The overarching aim of this research is to empirically test the effect of customer experience on customer perceived value and behavioral intentions while assessing the mediating role of customer perceived value. To achieve this aim, we collect data from 338 customers of restaurants in South Korea. The hypotheses intended to achieve this aim are tested using the structural equations modeling technique. The outcome of the research reveals that customer experience positively and significantly affects behavioral intentions. Additionally, customer experience has a significant positive effect on both hedonic and utilitarian value respectively. Hedonic value positively and significantly predicts behavioral intents while utilitarian value is negative but significantly related to behavioral intentions. The study further finds support for a mediating effect of hedonic value on the relationship between customer experience and behavioral intentions. The current study provides managerial and theoretical insights into understanding customer experience management, customer perceived value, and customer behavioral intentions.